Perbaikan Kualitas Toko Dunia Foto Dengan Metode Servqual, Zot (Zone Of Tolerance), Dan Siklus PDCA - Puspasari, Vina (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Toko Dunia Foto as a photography business in the city of Palembang that seeks to improve services to consumers due to a decline in consumers from September 2018 to July 2019 namely 50, 47, 52, 46, 51, 48, 47, 43, 37, 35, 32 One reason is the slow service of customer data employees. To overcome these problems the right method used is the ServQual, ZOT, and PDCA cycle. Based on the results of data processing using ServQual, it is known that each service dimension has a high negative gap of -0.96 tangibles, -0.97 responsiveness, -0.88 assurance, -0.90 empathy, and -0.98 reliability. The greater the negative gap obtained, the level of service far from consumer expectations. In the ZOT method it is known that all attributes are outside the tolerance zone. To minimize the gap, efforts were made to increase the prohibition of littering, speakers for music, making work instructions, and making a rating system. After repairing the gap, each dimension experienced an increase of -0.64 for the tangibles dimension, -0.80 reliability dimensions, -0.78 rensponsiveness dimensions, -0.79 assurance dimensions, and -0.80 emphaty dimensions.